Eficacia y seguimiento de las medidas de protección establecidas en la LOIPEVCM y el COIP, otorgadas por la Junta Cantonal de Protección de Derechos y la Unidad Judicial Multicompetente Penal con sede en el cantón La Joya de los Sachas dentro del periodo 2020-2021 - González Costa, Cristina Salomé (2023)
he main objective of this degree project entitled: Effectiveness and follow-up of the protection measures established in the LOIPEVCM and the COIP, granted by the Cantonal Board for the Protection of Rights and the Criminal Multicompetent Judicial Unit based in the canton of La Joya de los Sachas in the period 2020-2021, is to determine whether the protection measures granted in cases of gender-based violence are effective and whether there is a follow-up of these measures in the canton of Joya de los Sachas. Evidently, the problem lies in the lack of compliance with the norms and clarity of the guidelines regarding the follow-up of all protection measures granted to victims of violence or the lack of institutions that guarantee their true compliance and effectiveness in order to achieve the purpose of eradicating violence. Likewise, to ensure that the victim is genuinely protected and that there is no other act of violence against her within her family or in society. It should be emphasized that the State as guarantor of rights is responsible for ensuring the safety and integrity of Ecuadorian families and guarantee their rights and constitutional guarantees, as it is clear that violence in family spaces is a problem that is growing by leaps and bounds in our environment, which is why the Ecuadorian government must act in time and form the protection of these rights. It is for this reason that we have seen the need to analyze the effectiveness of the protection measures established in the LOIPEVCM and the COIP and whether there is a follow-up by State institutions in cases of violence against women and their families, and therefore the consequences of the lack of timely follow-up by the Ecuadorian State. Based on this, to propose to the Ministry of Women and Human Rights to reform the Regulation of the Law to Prevent and Eradicate Violence against Women so that an additional article is added, applicable to the follow-up of administrative protection measures where there must be collaboration with the different State entities in order to protect the victim of violence. Key words: COIP, LOIPEVCM, protection measures, victims of violence.